Specific understanding of the concept of war in the documentary-fictional cycle «Voices of utopia » by S. Alexievich - Tratsiak, Zoya I. (Journal of the Belarusian State University. Philology, 2019)
The article analyses new approaches to the theme in the cycle «Voices of utopia» by S. Alexievich. The place of the concept of war in the outlook of the former Soviet person is pointed out. Polyphony of this notion is highlighted. Ordinary storytellers identified it not only with the Great Patriotic War, the Afghan War or local wars that occurred in the time with the the Stalinist repression, elimination of consequences of the Chernobyl accident, Soviet collapse. Extreme importance of the individually marked verbal element derived by S. Alexievich from the interviews with witnesses of tragic events for the literature is traced out. Their personal impressions and experiences are connected with some knowledge obtained from works by B. Polevoi, A. Fadeev, E. M. Remarque, etc. It is noted that in a series of narrators in S. Alexievich’s cycle faced with the problem of adequate verbalisation of their experience in tragic circumstances. Finding no necessary linguistic resources, the interlocutors fell silent, listening to their psychological pain and enabling a professional to embody the quintessence of traumatic experiences in a documentary-fictional text.
Keywords: war theme; emergency; pathos of struggle; the tragic; confession; author’s concept; Belarusian literature; documentary-fictional work